Searching for sustainability : - Norton, Bryan G. (Cambridge University Press, 2003)
This book examines the setting of sustainability as a goal for environmental management. The author explores ways to break down the disciplinary barriers to communication and deliberation about environment policy, and to integrate science and evaluations into a more comprehensive environmental policy. The book appeals to students and professionals in the fields of environmental policy and ethics, conservation biology and philosophy.